Zika virus-induced neuro-ocular pathology in immunocompetent mice correlates with anti-ganglioside autoantibodies. Issue 9 (1st September 2020) - Beaver, Jacob T.; Mills, Lisa K.; Swieboda, Dominika; Lelutiu, Nadia; Esser, Edward S.; Antao, Olivia Q.; Scountzou, Eugenia; Williams, Dahnide T.; Papaioannou, Nikolaos; Littauer, Elizabeth Q.; Skountzou, Ioanna
ABSTRACT: A severe consequence of adult Zika virus (ZIKV) infection is Guillain-Barré Syndrome (GBS), where autoreactive antibodies attack peripheral and central nervous systems (CNS) resulting in neuro-ocular pathology and fatal complications. During virally induced GBS, autoimmune brain demyelination and macular degeneration correlate with low virus neutralization and elevated antibody-mediated infection among Fcγ-R bearing cells. The use of interferon-deficient mice for ZIKV studies limits elucidation of antibody-dependent enhancement (ADE) and long-term pathology (≥120 days), due to high lethality post-infection. Here we used immunocompetent BALB/c mice, which generate robust humoral immune responses, to investigate long-term impacts of ZIKV infection. A high infectious dose (1x10 6 FFU per mouse) of ZIKV was administered intravenously. Control animals received a single dose of anti-IFNAR blocking monoclonal antibody and succumbed to lethal neurological pathology within 13 days. Immunocompetent mice exhibited motor impairment such as arthralgia, as well as ocular inflammation resulting in retinal vascular damage, and corneal edema. This pathology persisted 100 days after infection with evidence of chronic inflammation in immune-privileged tissues, demyelination in the hippocampus and motor cortex regions of the brain, and retinal/corneal hyperplasia. Anti-inflammatory transcriptional responses were tissue-specific, likely contributing to differential pathology in these organs. Pathology in immunocompetent animals coincided with weakly neutralizing antibodies and increased ADE among ZIKV strains (PRVABC59, FLR, and MR766) and all Dengue virus (DENV) serotypes. These antibodies were autoreactive to GBS-associated gangliosides. This study highlights the importance of longevity studies in ZIKV infection and confirms the role of anti-ganglioside antibodies in ZIKV-induced neuro-ocular disease.